A case of Co-infection COVID-19 and influenza with psychotic symptoms. Issue 4 (April 2023) - Valikhani, Maryam; Feyzmanesh, Arghavan; Daliri, Salman
Abstract: Coronavirus disease 2019 (COVID-19), is a pandemic disease that has appeared in recent years with different symptoms and manifestations. This disease has Co-infection with other infections and has aggravated the symptoms in patients. This study was conducted with the aim of reporting a case of Co-infection COVID-19 and influenza with psychotic symptoms. In this study, the manifestations of a case of co-infection with COVID-19 and influenza with psychotic symptoms were discussed in Shahroud city in Iran in 2022. Based on this, the patient's laboratory, pathological and therapeutic findings were investigated. The patient, a 16-year-old boy, had symptoms of fever, chills, cough, body pain, and headache with seizures and delirium. Reverse transcription–polymerase chain reaction tests for covid-19 and influenza were positive, but no abnormalities were observed in laboratory variables and graphs. The patient was treated for psychotic disorders for 40 days and then recovered.